2020
DOI: 10.14529/hsm200209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Regular Physical Activity of Various Intensity on the Functional Status of 5–6 and 6–7-Year-Old Children

Abstract: Aim. The article aims to identify the effect of regular physical activity of medium and high intensity on the functional status of 5–6 and 6–7-year-old children. Materials and methods. The study involved children assigned for health reasons to the main medical group. A set of indicators characterizing the physiological, psychological, and behavioral aspects of the functional status was used. The experimental programs differed in the intensity of physical exercises. Results. Training programs based on high-inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…Particular attention is paid to the physical education of primary schoolchildren (Krivolapchuk & Chernova, 2019;Ivashchenko, 2020;Khudolii, Iermakov, & Bartik, 2020). Studies considered the issues of children's age-related development (Krivolapchuk, Chernova, & Gerasimova, 2020); Krivolapchuk, Gerasimova, Myshiakov, & Chicherin, 2020), learning process (Khudolii, Ivashchenko, & Chernenko, 2013;, motor abilities develop ment (Chernenko, 2009;Titarenko, 2010;Khudolii & Titarenko, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Particular attention is paid to the physical education of primary schoolchildren (Krivolapchuk & Chernova, 2019;Ivashchenko, 2020;Khudolii, Iermakov, & Bartik, 2020). Studies considered the issues of children's age-related development (Krivolapchuk, Chernova, & Gerasimova, 2020); Krivolapchuk, Gerasimova, Myshiakov, & Chicherin, 2020), learning process (Khudolii, Ivashchenko, & Chernenko, 2013;, motor abilities develop ment (Chernenko, 2009;Titarenko, 2010;Khudolii & Titarenko, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In research papers, motor activity is viewed as a necessary condition for developing cognitive functions and improving health-related quality of life (Evaristo, Moreira, Lopes, Abreu, Agostinis-Sobrinho, Oliveira-Santos, Póvoas, Oliveira, Santos, & Mota, 2018;Hsieh, Fung, Tsai, Chang, Huang, & Hung, 2018;Kaiser-Jovy, Scheu, & Greier, 2017). The importance of increasing primary schoolchildren's motor activity is pointed out by Krivolapchuk and Chernova (2019), Krivolapchuk, Chernova, & Gerasimova(2020), Krivolapchuk, Gerasimova, Myshiakov, & Chicherin (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Particular attention is paid to the physical education of primary schoolchildren (Krivolapchuk & Chernova, 2019;. Studies considered the issues of children's age-related development (Krivolapchuk, Chernova, & Gerasimova, 2020); Krivolapchuk, Gerasimova, Myshiakov, & Chicherin, 2020), learning process (Khudolii, Ivashchenko, & Chernenko, 2013;, motor abilities develop ment (Chernenko, 2009;Titarenko, 2010;Khudolii & Titarenko, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For their part, schools have integrated sport and psychology into educational training, motivating the work of the trainer (Mikhaylova, 2018). In this regard, a study focused on children from 5 to 7 years old showed that those who perform exercises with medium and high intensity showed favorable physiological, psychological and behavioral changes (Krivolapchuk et al, 2020). In secondary education, the impact of sports practice on physical development, adaptation skills, physical fitness, and functional status has also been evaluated.…”
Section: Introductionmentioning
confidence: 99%